2015
DOI: 10.1371/journal.pone.0128761
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Deletion of TAK1 in T Cells Reveals a Pivotal Role of TCRαβ+ Intraepithelial Lymphocytes in Preventing Lymphopenia-Associated Colitis

Abstract: The kinase TAK is required for the development of conventional and regulatory T cells. We previously reported that mice with conditional deletion of TAK1 in T cells (Lck-cre:TAK1fl/fl mice) exhibited severe T lymphopenia, and were nevertheless predisposed to spontaneous colitis with unknown etiology. Here we focused on the immunopathological mechanism in colitic Lck-cre:TAK1fl/fl mice. We found that ‘leaky’ CD4+ T cells retaining TAK1 acquired inflammatory phenotypes that contribute to disease onset in Lck-cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Analysis of Tak1 fl/fl Cd4 Cre mice confirmed the selective absence CD8αα IELs, but not TCRγδ + IELs in the small intestine ( Fig. 1c ), as previously reported 10 . Correspondingly, we observed a reduction of CD122 + H-2K b+ DN thymocytes in TAK1-deficient mice ( Fig.…”
Section: Resultssupporting
confidence: 89%
“…Analysis of Tak1 fl/fl Cd4 Cre mice confirmed the selective absence CD8αα IELs, but not TCRγδ + IELs in the small intestine ( Fig. 1c ), as previously reported 10 . Correspondingly, we observed a reduction of CD122 + H-2K b+ DN thymocytes in TAK1-deficient mice ( Fig.…”
Section: Resultssupporting
confidence: 89%
“…Previous work has supported the regulatory role of TAK1 in the production of cytokines including IL‐6 in murine embryonic fibroblasts 45 . Inhibition and inactivation of TAK1 has also been shown to impair cytotoxicity and cytokine and chemokine production in NK cells 63 ; on the other hand T cell‐specific knockout of TAK1 has resulted in an increase in the gene expression of IL‐6 and TNF among other pro‐inflammatory cytokines 64 . Inhibition of this spectrum of cytokines to the degree we detect is particularly supportive of the potential utility of targeting TAK1 activity therapeutically to down‐regulate allergic inflammation caused by activated mast cells.…”
Section: Discussionmentioning
confidence: 91%
“…The same group later found that in these mice TAK1 expression is retained in CD4 + T-cells. These cells acquire an inflammatory phenotype and continuous access to colon that result in pathogenesis in colitis (Sanjo et al 2015). Also, TAK1 in epithelial cells was protective in mouse colitis (Kajino-Sakamoto et al 2008;Kim et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…These cells acquire an inflammatory phenotype and continuous access to colon that result in pathogenesis in colitis (Sanjo et al. ). Also, TAK1 in epithelial cells was protective in mouse colitis (Kajino‐Sakamoto et al.…”
Section: Introductionmentioning
confidence: 99%